PENGARUH KONSENTRASI AWAL DAN PENAMBAHAN H2O2 TERHADAP EFEKTIVITAS DEGRADASI FOTOKATALISIS METHYLENE BLUE PADA FILM TiO2 - Akhiruddin Maddu (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2009)
Photocatalytic degradation of methylene blue (MB) in water using TiO2 film was investigated. TiO2 film was coated on glass substrate by squeegee printing method. TiO2 film has an anatase phase with crystallite size of 24.5 nm regarding to X-ray diffraction analysis result. Photocatalysis test was carried out in the static water bath containing Methylene Blue. TiO2 film on glass substrate placed in water bath with MB dye solution was exposed with UV light source. The Effects of concentration and pH of MB solution and H2O2 addition were investigated. Degradation of MB showed an optimal result for MB concentration of 5 mM. Addition of H2O2 into water could also increase the photocatalytic degradation of MB up to 84.2% with a degradation rate of 0.01 minute-1.